Chitosan-Reinforced MFC/NFC Aerogel and Antibacterial Property - Huanlei Yang; Shuxin Zhang; Jinhua Yan (Advances in Polymer Technology)
MFC/NFC aerogel has water sensitivity, and it should be improved in strength in water before application. Chitosan was investigated as a MFC/NFC aerogel reinforcing agent in this paper. The reinforced aerogel showed slightly tighter structure and very good water stability and mechanical strength. FTIR disclosed the chemical bonds formed between chitosan and cellulose. Nanoparticles of silver (Ag-NPs) were loaded using the reinforced aerogel. The excellent Ag-NP monodistribution on the aerogel was expressed by TEM. Both chitosan-reinforced Ag-NPs loaded MFC aerogel and NFC aerogel and expressed great antibacterial activity, though reinforced MFC aerogel exhibited better properties, like higher BET, lighter density, more Ag-NP loading, and better distribution, than NFC aerogel in this research. Chitosan-reinforced MFC aerogel is a good potential substrate for nanoparticle loading and biocomposite making.